Brachial plexus doses in locoregional radiotherapy for breast cancer - Goyal, Shikha; Menon, Durgapoorna; Puzhakkal, Niyas; Makuny, Dinesh (Therapeutic Radiology and Oncology, 2019)
Background: Brachial plexopathy is a known issue following axillary radiotherapy in locally advanced breast cancer (LABC). We attempted to adapt Radiation Therapy Oncology Group (RTOG) guidelines on brachial plexus (BP) contouring (head and neck cancer) to breast cancer patients receiving post-mastectomy locoregional radiotherapy (LRRT), to determine (I) feasibility of identifying BP in the treatment position for breast cancer, and (II) radiation therapy dose received by BP with respect to the planned dose. Methods: Planning computed tomography (CT) sets (non-contrast) of 10 LABC patients, who had undergone mastectomy and subsequently completed LRRT including posterior axillary boost, were retrieved. Treatment included chest wall irradiation [50 gray (Gy) in 25 fractions, 6–10 Mega-electronVolt (MeV) electrons, 80–100% isodose], and supraclavicular and axillary RT with an anterior photon field [6 megavolts (MVs), 40 Gy in 20 fractions] and a posterior axillary field (6 MVs, 10 Gy in 5 fractions). Vertebral bodies C5–T1, anterior and middle scalene muscles (MS) were contoured and used as guide to identify probable location of BP. Results: Ten LABC patients received LRRT (50 Gy). Mean ipsilateral BP volume was 13.8 cc. Medians of maximum and mean BP doses were 54.65 and 36.62 Gy, respectively. Mean global dose maximum of the respective plans was 58.83 Gy. Mean BP volume receiving >50 Gy was 27.81% (range, 13.01–51.80%). Conclusions: BP contouring in LABC radiotherapy is feasible, with uncertainty in regions of altered anatomy (C5–6, shoulder). The maximum BP doses always exceeded prescribed dose, and although lower than tolerance dose (66 Gy) should be evaluated to reduce adverse events’ risk. This study establishes the feasibility of following RTOG guidelines for BP contouring even in altered treatment position in breast cancer radiotherapy planned on non-contrast CT scans. BP dose maxima in conventional radiotherapy planning are nearly 18–20% higher than prescription isodoses. Albeit safe in conventional terms, the risk of high doses leading to increased risk of plexopathy warrants consideration especially with regard to relation to tumor boost volumes as well as when using hypofractionated regimens which may be less forgiving for late effects.